2011
DOI: 10.1111/j.1540-5885.2010.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

How Many and What Kind? The Role of Strategic Orientation in New Product Ideation*

Abstract: Existing studies on the role that strategic orientation plays in companies' innovation efforts primarily focus on identifying the relationship between strategic orientation and innovation performance for launched new products. In contrast, this article investigates how the different types of strategic orientation (i.e., customer, competitor, and technology orientations) influence the front end of innovation. Specifically, this research examines how strategic orientation relates to new product ideation outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 62 publications
(83 reference statements)
4
93
0
4
Order By: Relevance
“…It may therefore be deduced that business orientation adopted by firms in deploying resources may be a source of competitive advantage. This point was corroborated by Spanjol, Qualls and Rosa (2011), who described strategic orientation, which is a function of business orientation, as the direction adopted by a firm to create required behaviours to achieve targeted superior business performance. In fact, Zhou and Li (2009) described business orientation as a driver of superior performance Several business orientation dimensions have been identified in literature.…”
Section: Literature Reviewsupporting
confidence: 49%
See 2 more Smart Citations
“…It may therefore be deduced that business orientation adopted by firms in deploying resources may be a source of competitive advantage. This point was corroborated by Spanjol, Qualls and Rosa (2011), who described strategic orientation, which is a function of business orientation, as the direction adopted by a firm to create required behaviours to achieve targeted superior business performance. In fact, Zhou and Li (2009) described business orientation as a driver of superior performance Several business orientation dimensions have been identified in literature.…”
Section: Literature Reviewsupporting
confidence: 49%
“…What this suggests is that performance of organisations will depend on how business orientation fits organisational resources, as also corroborated by Spanjol et al (2011). The relationship between business orientation, life cycle and firm performance has been investigated in small and medium enterprises (Lester et al, 2008;Aragon-Sanchez and Sanchez-Marin, 2005), e-businesses (Koellinger, 2008), and in a cross industry-survey of consumer and business markets (Lester et al 2008;Morgan, Vorhies and Mason, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen and Kaimenakis (2007) reported that there are only a few studies that have been carried out on small and medium-sized enterprises in order to assess the existence of market orientation relationship to business performance. Spanjol, Qualls and Rosa (2009) mentioned that competitor and customer orientations are sometimes encompassed in the composite construct of market orientation. Narver and Slater (1990) concluded a positive relationship between market orientation and business profitability in a sample of product and service businesses operating in a variety of industries.…”
Section: Business Management and Strategymentioning
confidence: 99%
“…Among 100 new ideas, usually one becomes a successful product that reaches the market (COOPER; EDGETT, 2007). As a result, outcomes are negatively affected and resources are invested without delivering value (CHRISTENSEN;RAYNOR, 2003;KRISTENSSON;MAGNUSSON, 2010;MCCLELLAND, 2002a;SPANJOL;QUALLS;ROSA, 2011).…”
Section: Introductionmentioning
confidence: 99%